Valor nutritivo dos fenos de forrageiras nativas do pantanal para borregas Santa Inês - Lima, Levi Afonso Cavalcante de (2020)
The objective was to evaluate the chemical-bromatological composition and nutritional parameters of two native forages from the Brazilian Pantanal [Cerrado grass (Mesosetum chaseae Luces) and rice grass (Luziola subintegra Swallen)] preserved in the form of hay and, as a parameter, tifton grass hay 85 (Cynodon spp.) and brachiaria grass (Urochloa decumbens), for feeding Santa Inês ewe lambs. 16 nine-month-old ewe lambs were used, approximately and with an initial weight of 30.00 ± 2.50 kg, distributed in a completely randomized design, with four replications. The animals were fed exclusively with the four types of hays, in metabolic cages, with water permanently at ease. Brachiaria hay had the lowest levels of dry matter (DM) and crude protein (CP), while the highest CP content was found for rice grass hay in relation to the other evaluated hays. Although the highest content of neutral detergent fiber (NDF) was observed in brachiaria hay; cerrado grass hay showed the highest concentration of lignin. The values of total phenols and total tannins of the experimental hays showed values below 40 g kgMS-1. The grass hays of the forages native to the Pantanal showed a consumption of DM, NDF and total carbohydrates similar (P <0.05) to that of the tifton-85 and brachiaria hays. The lowest consumption of CP was obtained with animals fed with brachiaria grass. The digestibility of DM and CP was influenced by the type of hay offered, where rice grass showed higher values than those obtained with brachiaria grass, both similar to other hays. Cerrado grass showed greater digestibility for ether extract. The apparent digestibility of the other components did not differ (P <0.05) for the different hays offered. Foraging hay from the Pantanal has satisf